1998
DOI: 10.1093/emboj/17.12.3439
|View full text |Cite
|
Sign up to set email alerts
|

Transcription activation at Class II CRP-dependent promoters: identification of determinants in the C-terminal domain of the RNA polymerase alpha subunit

Abstract: Many transcription factors, including the Escherichia coli cyclic AMP receptor protein (CRP), act by making direct contacts with RNA polymerase. At Class II CRP-dependent promoters, CRP activates transcription by making two such contacts: (i) an interaction with the RNA polymerase alpha subunit C-terminal domain (alphaCTD) that facilitates initial binding of RNA polymerase to promoter DNA; and (ii) an interaction with the RNA polymerase alpha subunit N-terminal domain that facilitates subsequent promoter openi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
141
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(151 citation statements)
references
References 47 publications
10
141
0
Order By: Relevance
“…In class II CRP-dependent promoters, ␣-CTD makes nonspecific contacts with the DNA segment immediately upstream of the CRP site (16,23). In this study, we found that wild-type RNAP, but not RNAP with the ␣-CTD truncation, extends DNase I protection upstream of that protected by CooA alone.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…In class II CRP-dependent promoters, ␣-CTD makes nonspecific contacts with the DNA segment immediately upstream of the CRP site (16,23). In this study, we found that wild-type RNAP, but not RNAP with the ␣-CTD truncation, extends DNase I protection upstream of that protected by CooA alone.…”
Section: Discussionmentioning
confidence: 68%
“…This also suggests that the upstream A ϩ T-rich sequence of P cooF does not act as a UP element. Although we cannot exclude the possibility that some portion of the protection upstream of the CooA-binding site is due to a conformational change in CooA induced by the presence of RNAP, the interaction of ␣-CTD with DNA upstream of CooA is consistent with the sequence-nonspecific interactions between DNA and ␣-CTD observed at class II CRP-dependent promoters (23).…”
Section: Cooa Utilizes Protein-protein Contacts With ␣-Ctd To Facilitmentioning
confidence: 74%
See 2 more Smart Citations
“…Analysis of the high resolution crystal structure of a CRP⅐␣CTD⅐DNA ternary complex shows that AR1 contacts a segment of the surface of ␣CTD that is located on the opposite face from the 261 determinant (8). This surface, known as the 287 determinant, includes residues 285-289 that had been identified in previous genetic analyses as being the most likely residues in ␣CTD to make direct contact with CRP (19,20).…”
mentioning
confidence: 97%